Sialidase activity in aerobic vaginitis is equal to levels during bacterial vaginosis - Marconi, Camila [UNESP]; Donders, G. G G; Bellen, G.; Brown, D. R.; Parada, Cristina Maria Garcia de Lima [UNESP]; Silva, Marcia Guimarães da [UNESP] (Elsevier, 2013)
Objective: To evaluate levels of proinflammatory cytokines and sialidase activity in aerobic vaginitis (AV) in relation to normal vaginal flora and bacterial vaginosis (BV). Study design: In this cross-sectional study, a total of 682 consecutive non-pregnant women attending the gynecology service were assessed and 408 women were included. Vaginal rinsing samples were collected from 223 women with microscopic finding of BV (n = 98), aerobic vaginitis (n = 25) and normal flora (n = 100). Samples were tested for interleukin (IL)-1β, IL-6, IL-8, tumor necrosis factor (TNF)-α, and sialidase activity. Results: Compared to women with normal flora, vaginal levels of IL-1β were highly increased in both BV and AV (p < 0.0001). Significantly higher vaginal IL-6 was detected in AV (p < 0.0001) but not in BV, in relation to normal flora. Women with AV also presented increased IL-8 levels (p < 0.001), while those with BV presented levels similar to normal flora. Sialidase was increased in BV and AV compared with the normal group (p < 0.0001) but no difference in sialidase activity was observed between BV and AV. Conclusion: A more intense inflammatory host response occurs for AV than for BV when compared with normal flora. Furthermore, the increased sialidase activity in AV and BV indicates that both abnormal vaginal flora types can be harmful to the maintenance of a healthy vaginal environment. © 2012 Elsevier B.V.
Keywords: Aerobic vaginitis; Bacterial vaginosis; Cytokine; Sialidase; Vaginal innate immunity; interleukin 1beta; interleukin 6; interleukin 8; sialidase; tumor necrosis factor alpha; adult; concentration (parameters); controlled study; cross-sectional study; enzyme activity; female; human; major clinical study; pH; priority journal; protein expression; vagina flora; vaginitis; Adolescent; Adult; Bacteria, Aerobic; Bacterial Proteins; Brazil; Cross-Sectional Studies; Female; Humans; Interleukin-1beta; Interleukin-6; Interleukin-8; Middle Aged; Molecular Typing; Mucous Membrane; Neuraminidase; Up-Regulation; Vagina; Vaginal Smears; Vaginosis, Bacterial; Young Adult